(untitled) (Journal of Computational Mathematics, 1983)
A k-step, (k+2)th order two-stage implicit hybrid method which has all the advantages of Enright's method but not its principal disadvantages is proposed. A "simple" approach to estimate the local truncation error is developed. Preliminary numerical results indicate that the hybrid method compares favorably with Enright's method.